43 Years Old Female with Acquired Hemophilia Presented with Pseudotumor - Ward, Shinta Oktya; Fianza, Pandji Irani (Bioinformatics and Biomedical Research Journal, 2018)
Introduction: Acquired-haemophilia A in women is rare. This disorder is caused by the formation of auto-antibodies to factor VIII. Pseudo-tumor is a complication of hemophilia caused by recurrent bleeding which forms mass due to the presence of blood and necrotic tissue.A woman, 43 years old with complaints of left thigh lumps for 2 weeks before admitted to the hospital. Physical examination found a mass in the left thigh, with a thigh circumference of 34 cm, cystic. Laboratory tests showed coagulation disorders in the form of normal APTT lengthening after a mixing study, 2% factor VIII and 7.12 BU inhibitor levels. The ultrasound results of the femoral region showed heterogeneous cystic lesions with multi-inoculated internal echo and septa in the subcutaneous, the impression involved a muscular layer. Vascularity did not appear in it. The patient was improved with conservative therapy of 500mg corticosteroids and recombinant factor VIII. Pseudotumor hemophilia must be followed up immediately since it may cause further complications in the form of compartment syndrome. A biopsy is contraindicated in pseudotumor hemophilia. Simple imaging modalities are able to distinguish pseudotumor from other tumors. The patient was improved with conservative corticosteroid pulse dose 500g for inhibitor and recombinant factor VIII therapy. Due to limited costs, Recombinant activated factor VIII combined with activated prothrombin complex concentrate was not given.Acquired hemophilia A is a hemorrhagic disease with reduced coagulation factor VIII (F.VIII) activity due to the appearance of autoantibodies (inhibitors) against F.VIII. Hematoma is generally diffuse and very painful (Pseudomotor). In contrast to congenital hemophilia, where joint bleeding rarely occurs in AHA. The two strategies used for the management of AHA with pseudotumor in this patient is hemostatic therapy and immunosuppression.